Implementation of the Frame-Based LSB Steganography Method for Embedding Secret Messages in Digital Video Media - Jhonatan Antonius Purba; Theresya Simanjuntak; Jelita Astrid Gulo (BIOS: Jurnal Informatika dan Sains, 2025)
The advancement of information technology has created a growing need to protect confidential data from unauthorized access. Steganography is a technique for hiding information within digital media so that its existence cannot be detected. This study implements a Frame-Based Least Significant Bit (LSB) steganography method to embed secret messages into digital video media in AVI format. This method works by extracting frames from the video, modifying the least significant bit of pixel values in the blue channel of each frame, and then reconstructing them back into a video. The implementation was carried out using the Python programming language, with the OpenCV library for video manipulation and CustomTkinter for the user interface. The testing results show that the system is capable of embedding and extracting messages with a 100% success rate in AVI videos using the FFV1 (lossless) codec. The embedding capacity depends on the video resolution and the number of frames. A video with a resolution of 1920×1080 at 30 fps for 10 seconds can store up to 207,360,000 bits or approximately 24 MB of data. This method preserves the visual quality of the video with changes that are imperceptible to the human eye.